Cardiac arrhythmias associated with umbilical venous catheterisation in neonates - Verheij, Gerdina (BMJ Publishing Group, 2009)
Umbilical venous catheters (UVCs) are commonly used in the management of severely ill neonates. Several life-threatening complications have been described, including catheter-related infections, myocardial perforation, pericardial effusion and cardiac arrhythmias. This report describe two neonates with cardiac arrhythmias due to umbilical venous catheterisation. One neonate had a supraventricular tachycardia requiring treatment with intravenous adenosine administration. Another neonate had an atrial flutter and was managed successfully with synchronised cardioversion. The primary cause of cardiac arrhythmias after umbilical venous catheterisation is inappropriate position of the UVC within the heart and the first step to treat them should be to pull back or even remove the catheter. Cardiac arrhythmia is a rare but potentially severe complication of umbilical venous catheterisation in neonates.